Thoracoscopic management of symptomatic esophageal mucocoele after esophageal exclusion - Thapa, B; Sapkota, R; Sayami, P (Nepal Journal of Medical Sciences, 2013)
Surgical exclusion of the thoracic esophagus is done to avoid mediastinal soiling in esophageal tears when patients present late. Esophageal exclusion can result in the accumulation of secretions and dilatation of the esophageal remnant leading to an esophageal mucocele. Although it is usually asymptomatic, if it increases in size it can produce a variety of compressive symptoms such as coughing, chest pain and respiratory distress. We present a case of symptomatic mucocele after esophageal exclusion treated successfully with thoracoscopic resection. Surgical resection should be considered for symptomatic patients, and thoracoscopy offers minimally invasive and less painful alternative to thoracotomy in these patients. Nepal Journal of Medical Sciences | Volume 02 | Number 02 | July-December 2013 | Page 181-183 DOI: http://dx.doi.org/10.3126/njms.v2i2.8972